(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the pedagogical and psychological conditions for the development of professional and pedagogical creativity of teachers of primary education, the formation of creative qualities for the effective implementation of their professional activities, the full compliance with the requirements of today’s reforms, competitive, abrupt changes in industry. There is a huge pedagogical and psychological potential in the training of primary school teachers, their professional and creative formation, the formation and development of personal creativity. The issues of organization, the organization of the professional creativity of future primary school teachers have a special place due to their versatility and complex structure.